DUKUNGAN PEMERINTAH DAERAH, OPTIMALISASI ASSET DAN PROFESIONALISME UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) - Komang Adi Kurniawan Saputra; A.A Ketut Jayawarsa; Putu Budi Anggiriawan (Universitas Airlangga, 2019)
The aim of this research is to examine the factors influencing the original income level of the villages by taking the research location in the villages managing the village fund in Buleleng-Bali Regency. Total number of 129 villages. The number of samples used in this study is equal to the number of population, The sampling technique in this study was total sampling. Meanwhile, to test the hypothesis using multiple linear regression with OLS model (Ordinary Least Square). The results obtained in this study indicate that Local Government Support, Optimalization of Village Asset Utilization and Professionalism of Village Asset Management have a significant effect on original income of the village. The contribution of this theoretical research is to contribute theoretical enrichment that underlies the increase of village original income and its practical contribution, this research can be one of reference for village apparatus, village counselor, and local government in making policy related to asset management or village property